A Rare Case Report of an Autonomous Thyroid Nodule (ATN) in a Young Woman from Bali: Restoration of Thyroid Uptake and Improvement in Thyroid Function After Radioactive Iodine (RAI) Therapy - W. Riski Widya Mulyani; Putu Ayu Sri Saraswati; Priska Gusti Wulandari; Ni Wayan Meindra Wirtayani; Lisa Herawati Diah (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Introduction: Autonomic thyroid nodules (NTOs) are hot nodules that produce thyroid hormones independently of TSH, suppress the surrounding parenchyma, and can give rise to subclinical or manifest hyperthyroidism. Radioactive iodine (RAI) is the definitive non-surgical therapy of choice due to its effectiveness and safety. A 29-year-old woman with a 3-year-old progressive right neck lump, asymptomatic, taking methimazole 2.5 mg/day routinely. Initial examination (May 2023) showed right ATN with subclinical hyperthyroidism (TSH <0.002 uIU/mL, fT4 1.90 ng/dL, benign isoechoic solid nodule ultrasound results, and right solitary hot nodule on SKG (thyroid scintigraphy) with left lobe suppression). RAI (NaI-131 15 mCi) was administered in November 2024 and 6 months thereafter there was a faint recovery of uptake in the left lobe. TSH/FT4 serial conducted: February 2025 (3 months post-RAI) 0.18/0.66; May 2025 (6 months post-RAI) 0.25/0.77; July 2025 (9 months post-RAI) 0.37/0.75. The nodules shrink without additional therapy. SKG (thyroid scintigraphy), alongside laboratory and ultrasound findings, is adequate for the diagnosis of ATN. The selection of RAI over other modalities was consistent with the size of these patients' nodules and comparative evidence of faster improvement in thyroid function and higher success rates. Post-RAI response as expected (uptake recovery in suppressed lobes accompanied by gradual improvement of TSH/fT4). The risk of NTO malignancy is low, so FNAB is not routinely performed, but post-RAI sonographic monitoring remains essential. SKG allows reliable diagnosis of NTO in young women. RAI provides biochemical improvement as well as expected recovery of extranodular uptake, with the need for structured monitoring to detect hypothyroidism and changes in nodule volume.